THE ROLE OF DEBATE IN THE ACADEMICDEVELOPMENT OF UNIVERSITY STUDENT - Axmedjanova Farida Djavairovna (Western European Studies, 2025)
the present article discusses the central role debate plays in university students' academic growth. Using a review of different educational frameworks, the article identifies how debate encourages critical thinking, improves communication skills, and encourages collaborative learning. By taking part in structured debates, not only do the students gain better insight into challenging topics, but they also have the confidence to express their ideas clearly. The results of this study indicated that debate in the curriculum of education will bring about a lot of impact on the students overall academic and personal development preparing them for future professional challenges.
Keywords: academic development; critical thinking